Raising awareness of alcohol as a modifiable risk factor for breast cancer: A randomized controlled trial comparing the efficacy of accessing an interactive website with a non-interactive website - Claudia Sardu; Fabrizio Angius; Paolo Contu; Sofia Cosentino; Monica Deiana; Matteo Fraschini; Clelia Madeddu; Elena Massa; Alessandra Mereu; Luigi Minerba; Carola Politi; Silvia Puxeddu; et al. (Breast)
Background: Alcohol consumption is a potentially modifiable risk factor for breast cancer (BC). Reducing alcohol consumption within the daily amount at low-risk for alcohol-related consequences (daily alcohol threshold) may contribute to preventing BC new cases. However, most women are unaware of risk factors for BC, the daily alcohol threshold, and how to measure alcohol use. We aimed at investigating the efficacy of accessing an interactive website in increasing the knowledge that alcohol is a BC risk factor. Methods: We conducted a randomized controlled trial among women waiting for mammography. Women completed a questionnaire to investigate their knowledge before and after accessing an interactive (intervention group) and non-interactive (control group) website. Results: We recruited 671 women, randomized 329 (49.0 %) and 342 (51.0 %) to the intervention and control groups, respectively. At baseline, most women were not aware of most modifiable BC risk factors. Accessing either website significantly increased the percentage of women who acquired the knowledge on BC risk factors, with the interactive website achieving better results: 82 % and 69 % of women acquired the knowledge that alcohol is a risk factor for BC in the intervention and control groups, respectively (p < 0.001). Among women with lower levels of education, the probability of acquiring this knowledge was higher in the intervention group than control group. Conclusion: Our results show that accessing an interactive website may increase the percentage of women who acquire the knowledge that alcohol is a BC risk factor especially among women of lower levels of education.